2022
DOI: 10.3389/fgene.2022.989779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical neutrophil-associated genes as reliable predictors of hepatocellular carcinoma

Abstract: Background: Growing evidence suggests that infiltrating neutrophils are key players in hepatocellular carcinoma (HCC) tumor progression. However, a comprehensive analysis of the biological roles of neutrophil infiltration and related genes in clinical outcomes and immunotherapy is lacking.Methods: HCC samples were obtained from the TCGA and GEO databases. The CIBERSORT algorithm was used to reveal the TIME landscape. Gene modules significantly associated with neutrophils were found using weighted gene co-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…PDZD4 has been identi ed as a biological target in various tumors. For instance, a study on hepatocellular carcinoma demonstrated that PDZD4, as a neutrophil-related gene, is a reliable predictor for hepatocellular carcinoma and its expression levels are positively correlated with patient survival [32] .…”
Section: Discussionmentioning
confidence: 99%
“…PDZD4 has been identi ed as a biological target in various tumors. For instance, a study on hepatocellular carcinoma demonstrated that PDZD4, as a neutrophil-related gene, is a reliable predictor for hepatocellular carcinoma and its expression levels are positively correlated with patient survival [32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest that high TMB levels often correspond to a poor prognosis in HCC patients. It has also been shown that HCC usually has lower TMB levels compared to other common tumors ( 65 ) and that high TMB is a predictor of poor prognosis in HCC patients after radical hepatectomy ( 66 ). However, the exact mechanism of effect remains unclear and more basic studies are needed to explore and demonstrate it.…”
Section: Discussionmentioning
confidence: 99%